STRATEGI PENGEMBANGAN DAN PEMASARAN KOMODITAS KOPI DI DESA KAONGKE-ONGKEA KECAMATAN PASARWAJO - Waode Alzarliani; La Ode Muhammad Mustari (Media Agribisnis, 2020)
The coffee development strategy in Kaongke-ongkea village is dominant in the valley area and is still limited to sloping areas. Although the water potential is very large, coffee processing in Kaongke-ongkea village is not yet electrically based. This is caused by undeveloped farmer institutions (BPTP Balitbang, Southeast Sulawesi, 2016). Facilities and infrastructure provide a very important role in supporting economic activities in the village of Kaongke-ongkea. The differences in the spatial patterns of land area, labor, production, and farmer capital are very important. If this can be optimized, it can maximize greater profits for the Kaongke-ongkea Village in particularly and Pasarwajo Sub-district in general. The aditional value of a commodity provides a very important role for regional economic growth so that in the development of an area it must pay attention to the issue because it can harm the regional economy (Bendavid-Val, 1991). The fundamental thing besides the marketing aspect is the large transportation costs incurred by coffee farmers due to the long distance from the coffee plantation to the market. Differences in the distribution of coffee commodities in various locations cause costs (Rustiadi et al. 2011). The pattern of the distribution of the amount of income and the level of knowledge of coffee processing has an impact on the pattern of demand for coffee commodities. These differences in spatial patterns make inter-regional linkages very important for the stability of the economy of Kaongke-ongkea Village. In addition, the type of coffee industry tree character needs to be known in determining the extent of farmers' knowledge and technology used in coffee processing so that the added value of coffee from Kaongke-ongkea Village can be increased to certified processing (brand). Coffee producers certify products to increase the added value of coffee so that the character of the authenticity of the product based on its origin can be maintained (Botelho et al. 2017). Keywords: Development strategy, coffee, marketing, SWOT